Error Analysis on Noun Phrase in Students’ Undergraduate Theses - Syafutri, Tania; Syafryadin, Syafryadin; Sofyan, Dedi (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The aim of this research is (1) to analyze the components of noun phrase errors that are often made by students in the introduction parts of their undergraduate theses, (2) to analyze the types of noun phrase errors that are often made by students in the introduction parts of their undergraduate theses, (3) to find out the differences between noun phrase errors made students in the introduction parts of their undergraduate theses. The method used in this research was mix method. The instrument comprised observation and documentation. The result of this research was as follows: (1) the most dominant component of noun phrase error made by UPI and Unib students in the introduction parts was a head error, (2) the most dominant type of error in noun phrases made by UPI was addition error; however, the most dominant type of noun phrase errors among Unib students was omission error, (3) the number of noun phrase errors in Unib was higher than those in UPI. It is recommended that students improve their mastery of noun phrases, that lecturers teach students how to write the introduction well, specifically on noun phrases, and that next researchers investigate additional aspects of noun phrases.Â